Poly(lactic acid) (PLA) – Short review of synthesis methods, properties, recent progress, and new challenges - Konrad Stefaniak; Anna Masek (eXPRESS Polymer Letters)
This review is focused on recent achievements in poly(lactic acid) (PLA) synthesis and copolymerization with special regard to biotechnological routes of PLA synthesis, which use bacteria/enzymes (e.g., enzymatic ring opening polymerization (eROP)). Besides PLA, also lactic acid (LA) synthesis is described and an emphasis is put on the biotechnological methods. Having regard to PLA copolymerization, this paper attempts to describe different types of PLA copolymers (such as block copolymers, PLA copolymers with polysaccharides, PLA-cellulose copolymer composites, and PLA polymer brushes). A detailed overview of the recent accomplishments in the field of PLA copolymers is presented. Various enhanced properties and applications of presented PLA copolymers are discussed. The attention is placed mainly on applications in the field of tissue engineering, drug delivery systems, and the packaging sector. Furthermore, a PLA market study and its economic forecast are presented. Eventually possible directions for future research in the field of PLA synthesis and copolymerization are indicated.